Cannabinoids and their medicinal potential - Tikoo, Deepika; Sharma, Geeta; Gupta, Meenakshi (International Journal of Basic & Clinical Pharmacology, 2017)
Cannabis sativa L preparations have been used therapeutically since many years. Inspite of their medicinal value, the danger of its abusive potential led to the ban on its use in clinical practice in many countries. The recent research and in depth knowledge about the cannabinoid system which throw a light on their disease management potential has paved way for the cannabinoids to become a new therapeutic focus of attention. Cannabinoids are a group of compounds that mediate their effects through cannabinoid receptors which include CB1, predominantly expressed in the brain and CB2 which is primarily found in the cells of the immune system. Despite the addictive properties of cannabis, the therapeutic value of cannabinoids is too high to be put aside. Numerous diseases such as anorexia, pain, inflammation, obesity, cardiovascular disorders, neurodegenerative diseases, cancer, gastrointestinal diseases, hepatic disorders, skin related diseases, respiratory disorders like asthma and eye diseases like glaucoma have suggested cannabinoid agonists/ antagonists/ cannabinoids related compounds as potential treatment options. Developments of new specific ligands for the cannabinoid receptors are now underway and it needs to be seen, if in future, they can prove to be a boon for the medical world. The paper reviews the current understanding of the cannabinoid receptors, their ligands and their possible role in various diseases supported by preclinical and clinical studies.